INCREASING RELIGIOUS AWARENESS IN EARLY CHILDHOOD THROUGH RELIGIOUS LITERACY PROGRAMS AT LUKMAN HAKIM PURWOKERTO KINDERGARTEN - Prawening, Cesilia; Hamid Samiaji, Mukhamad; Husnifah, Hikmatul (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2024)
Religious awareness in early childhood is an important foundation in the formation of children's character and morals. At this stage, children are at a critical phase in their cognitive and emotional development, where basic values and moral principles begin to take shape. This research aims to find out how to improve the religious basics of early childhood through religious literacy programs. The research uses qualitative methods with observational data collection techniques, interviews, and documentation. The data analysis used is the Miles and Huberman model, namely data reduction, display, and verification. The results of this study show that Bntuk and the main components of the religious literacy program at Lukman Hakim Purwokerto Kindergarten, include: daily activities, religious stories or stories, worship practice activities, creative and artistic activities, celebration of religious holidays, strengthening spiritual and social values, and collaboration with parents. Efforts made to increase religious awareness through religious literacy programs at Lukman Hakim Purwokerto Kindergarten are by 1) Introducing and getting used to religious practices, 2) Introducing and getting used to honest, helpful, polite, respectful, and sportsmanlike behavior, 3) Introducing and getting used to personal hygiene and environmental cleanliness, 4) Introducing religious holidays, 5) Daily activities to teach religious values, and 6) Introduce and foster respect and tolerance for other religions.